Towards the internet of agents: an analysis of the internet of things from the intelligence and autonomy perspective (2018)
Recently, the scientific community has demonstrated a special interest in the process related to the integration of the agent-oriented technology with Internet of Things (IoT) platforms. Then, it arises a novel approach named Internet of Agents (IoA) as an alternative to add an intelligence and autonomy component for IoT devices and networks. This paper presents an analysis of the main benefits derived from the use of the IoA approach, based on a practical point of view regarding the necessities that humans demand in their daily life and work, which can be solved by IoT networks modeled as IoA infrastructures. It has been presented 24 study cases of the IoA approach at different domains ––smart industry, smart city and smart health wellbeing–– in order to define the scope of these proposals in terms of intelligence and autonomy in contrast to their corresponding generic IoT applications.